Aldosterone induced macrophage movement through IL-6/Rho-ROCK pathway. (June 2015) - Wu, Xue-Ming; Chou, Chia-Hung; Chen, Ying-Hsien; Hung, Chi-Sheng; Tzeng, Yu-Lin; Wu, Vin-Cent; Ho, Yi-Lwun; Wu, Kwan-Dun; Lin, Yen-Hung
Abstract : Background/aim: Primary aldosteronism (PA) patients are correlated to higher cardiovascular events, endothelial function, and altered cardiac structure. Macrophage-mediated low grade inflammation plays important role of aldosterone-induced myocardial and vascular fibrosis. However, theeffect of aldosterone on macrophage movementis still unclear. Methods: We investigated the effect of aldosterone on macrophage movement and its mechanism. We used THP-1 as cell model of macrophage, and transwell assay to evaluate the migration and infiltration of cell. Two periods (16 hour and 48 hour) wereused to evaluate the migration and infiltration of macrophage. Results: Aldosterone increased THP-1 migration and infiltrationsince 10 −8 M at 48 hours but not 16 hours. Aldosterone induced both galectin-3 and IL-6 production in THP-1 cell. In contrast, aldosterone does not affect the production of matrix metalloproteinase-2 and tissue inhibitor of metalloproteinase-1in THP-1. The increased migration and infiltrationby aldosterone was inhibited partially by IL-6 siRNA but not galectin-3 siRNA. Aldosterone also induced Rho-ROCK up-regulation but also partially inhibited by IL-6 siRNA. The aldosterone induced cell migration and infiltration was blocked by Y27632 (Rho-ROCK inhibitor). Conclusions: Aldosterone increased microphage migration and infiltration. The process was partially involved IL-6/Rho-ROCK pathway.